2000
DOI: 10.1002/1097-4636(200010)52:1<77::aid-jbm10>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of biological tissues with a naturally occurring crosslinking agent: Fixation rate and effects of pH, temperature, and initial fixative concentration

Abstract: In an attempt to overcome the cytotoxicity problem of the glutaraldehyde-fixed tissues, a naturally occurring crosslinking agent (genipin) was used by our group to fix biological tissues. The study was intended to investigate the rate of tissue fixation by genipin. Glutaraldehyde was used as a control. In addition, the degrees of tissue fixation by genipin at different pHs (pH 4.0, pH 7. 4, pH 8.5, or pH 10.5), temperatures (4 degrees C, 25 degrees C, 37 degrees C, or 45 degrees C), and initial fixative concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 19 publications
4
71
0
2
Order By: Relevance
“…The bacterial collagenase enzyme degraded collagen by hydrolyzing the peptide bond on the amino-terminal side of glycine (-X-Gly-Pro) (44). Use of a commercially available purified bacterial collagenase has been used previously to degrade collagenous tissues (25,40). Following cross-linking of collagen, the sites of collagenase attack may be hidden or modified, and this contributes to the significant difference in the release of amino acid residues following enzymatic degradation (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial collagenase enzyme degraded collagen by hydrolyzing the peptide bond on the amino-terminal side of glycine (-X-Gly-Pro) (44). Use of a commercially available purified bacterial collagenase has been used previously to degrade collagenous tissues (25,40). Following cross-linking of collagen, the sites of collagenase attack may be hidden or modified, and this contributes to the significant difference in the release of amino acid residues following enzymatic degradation (21).…”
Section: Discussionmentioning
confidence: 99%
“…On the 8th day, the medium was removed from the wells, and the biofilm was carefully washed once with sterile deionized water to remove the dead cells. The biofilm was sensitized with 1 ml of RB (10 M) or CSRB (0.3 mg/ml) at 37°C for 15 min and irradiated at different doses (20,40, and 60 J/cm 2 ). Dark toxicity was evaluated after the sensitization period with the two photosensitizers.…”
Section: Fig 1 Schematic Of the Chemical Reaction During Conjugation mentioning
confidence: 99%
“…Then join the gelatin, we fabricated the scaffolds cross-linked by genipin under different freeze-dried temperatures. Genipin can spontaneously react with the amine groups on amino acids or proteins to form dark blue pigments 19) . The change of color in SF-G scaffolds cross-linked with genipin indicates microstructure changes during crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported that genipin reacts slowly in phosphate buffer solution with 98% of primary amines after 3 days, when the genipin concentration is 0.3% w/v and temperature $378C [13].…”
Section: Discussionmentioning
confidence: 99%
“…Genipin powder was stirred in deionized water at 58C for approximately 24 hours until a uniform suspension was obtained and subsequently heated at 378C for 30 minutes to partially dissolve the genipin without inactivating it [13]. The initial genipin concentration could not exceed 1% (w/v), due to the limited solubility of the crosslinker in aqueous solutions.…”
Section: Solder Preparationmentioning
confidence: 99%